Different mechanical responses of dimorphic forms of anthracene schiffbase crystal - Lakshmipathi, Madhumathi; Tothadi, Srinu; Emmerling, Franziska; Bhattacharya, Biswajit; Ghosh, Soumyajit (Journal of Molecular Structure, 2022)
We obtained concomitant dimorphic forms of Anthracene Schiffbase (N-(anthracen-9-yl methylene)-2,5dichloroaniline) from hexane solvent. Two polymorphs can be differentiated by their morphology and mechanical properties. One form is long acicular type and elastically bendable while another form is block shaped and brittle in nature. Mechanical property is attributed to underlying crystal packing. Hirshfeld analysis and energy framework calculations were done to corroborate structure-property correlation of two forms (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Anthracene schiffbase; Dimorphs; Elasticity; mechanical properties

Simultaneously mechanically flexible, photobending, and acidochromic cyanostilbene molecular crystals - Parthasarathy, Thiyagaraj; Mishra, Manish Kumar; Bhattacharya, Biswajit; Emmerling, Franziska; Ghosh, Soumyajit (Crystal Growth & Design, 2024)
Molecular crystals that respond to multiple stimuli are gaining significant attention for their potential in smart materials like actuators and sensors. However, imparting multiple stimuli-responsive properties to a single crystal remains a major challenge. Herein, we report two cyanostilbene derivative-based crystals 1 and 2, with various responses to stimuli such as mechanical stress, light, acid vapors, etc. Both crystals 1 and 2 demonstrated mechanical flexibility and reversible acidochromism. Additionally, crystal 1 also exhibited light-induced photobending, which is ascribed to Z to E photoisomerization. Detailed structure-property correlation was established to unravel distinct mechanical responses. The development of these multitasking crystals may find applications in multitasking actuators, anticounterfeiting materials, and more.